A Relational Study of Critical Threats and Risks Affecting the Potential Usage of Collaborative Pattern - Hina, S. (Global Institute of Flexible Systems Management, 2016)
With increased variety of collaborative tools offering advanced features, knowledge sharing among professional and social peers has become independent of space and time. This paper identifies the potential of social networks for educational collaboration among school stakeholders. It also draws an attention towards crucial threats and risks associated with the oblivious use of this online collaborative pattern. Cyber security issues are classified; showing high impact on the acceptance and intentional use of social networking sites (SNS). Influence of security and privacy issues on a trusted participation of stakeholders in a collaborative environment is discussed in the light of comprehensive review of literature. Conclusively all devised research hypotheses were supported using structural equation modelling techniques. Moreover, this research study discusses the research questions and investigated research findings. It is suggested that vigilant dealing with possible cyber-crimes and following the best practices for safe and secure SNS usage can lead towards operative use of this participatory platform in an educational paradigm. Â© 2016, Global Institute of Flexible Systems Management.